Realism and Reality Studies in the German Novelle of Poetic Realism - Silz, Walter (UNC Studies in the Germanic Languages and Literatures, 1954)
In this 1954 study of poetic realism and the "Novelle" form, Silz examines nine "Novellen" by Brentano, Arnim, Droste-Hülshoff, Stifter, Grillsparzer, Keller, Meyer, Storm and Hauptmann. Through his textual interpretation of each of these works Silz draws the threads of the transition from Romanticism to Naturalism as well as the development of the "Novelle" form.